Teleradiology service for mission hospitals: initial experiences in Ethiopia and Kenya - Matthew Larrison; Stanley G. Cheng; Stephen McManus (Health for All Nations, 2016)
Throughout their history, mission hospitals have provided high quality and lifesaving medical care to regions of the world where medical care is sparse. These hospitals are generally built and equipped through a combination of governmental and non-governmental sources. As advances in diagnostic medical imaging have progressed and become mainstream in the developed world, mission hospitals have adopted advanced imaging modalities. These modalities provide early diagnosis and treatment options for their patients. In addition to the installation and operation of advanced imaging equipment, the need for professional expert interpretation of these studies remains a challenge for mission hospitals. Historically these hospitals have used either voluntary services on site or paid for interpretations from local radiologists; however, with the introduction of high speed internet, teleradiology has become a possibility. This article describes the teleradiology experience of two mission hospitals in rural Africa.